Pengelolaan Sarana dan Prasarana Pendidikan di Madrasah Tsanawiyah Nurul Ihsan Kabupaten Batanghari - Suci Lailatul Hasanah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study focuses on the management of educational facilities and infrastructure at Madrasah Tsanawiyah Nurul Ihsan in Batanghari Regency. The method used is qualitative descriptive research with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the management of facilities and infrastructure at Madrasah Tsanawiyah Nurul Ihsan has been carried out quite well in accordance with applicable procedures, although the managers do not yet fully possess specialized competencies in the field of facilities and infrastructure, and there are still some facilities that have not been optimally fulfilled. The management process starts from the planning and procurement stage, utilization, maintenance, and care adjusted to the results of needs analysis and availability of funds. The main obstacles faced in management include limited funding, human resources, and limited space or location. Efforts made to overcome these obstacles include activities such as inventory management, implementation of maintenance programs, and organizing training for facilities and infrastructure managers. The researcher recommends that the management of facilities and infrastructure in madrasahs be carried out continuously with regular evaluations, so that the effectiveness and efficiency of management can continually improve in accordance with established procedures.